Is low body mass index a risk factor for semen quality? A PRISMA-compliant meta-analysis. Issue 32 (August 2019) - Guo, Dan; Xu, Min; Zhou, Qifan; Wu, Chunhua; Ju, Rong; Dai, Jiazhen
Abstract: Background: Male infertility has become a worldwide public health problem. However, the effect of low body mass index (BMI) is still controversial. Methods: Relevant articles in Pubmed, Embase, Web of science, and Wanfang database published until September 2017 were searched without language restriction. We performed a meta-analysis about low BMI and semen parameters containing total sperm count, concentration, semen volume, and sperm motility (overall and progressive), including 709 men with low BMI and 14, 622 men with normal BMI. Results: Thirteen studies were included in this meta-analysis and a total of 15, 331 individuals were accumulated. We pooled data from these articles and found standardized weighted mean differences in semen parameters (total sperm count and semen volume) showed significant difference between low BMI and normal BMI. Conclusions: This systematic review with meta-analysis has confirmed that there was a relationship between low BMI and semen quality, which suggesting low BMI may be a harmful factor of male infertility. Yet lacking of the raw data may influence the accuracy of the results. Further researches are needed to identify the role of underweight in male sterility.